(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
In education, using didactic games helps to develop students’ reading skills and facilitates the process of acquiring new knowledge in an engaging and effective manner. This article discusses the significance of didactic games in developing reading skills of primary school students and the approaches that should be used to conduct reading lessons with them.